Faktor yang Berhubungan dengan Kualitas Hidup Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis - Sitti Rahmah; Maryunis; Ernasari (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
Patients diagnosed with chronic kidney disease have various clinical problems and complications, which negatively affect the physical and biopsychosocial aspects that can affect the patient's quality of life. This study aims to determine the factors related to the quality of life of patients with chronic kidney disease undergoing hemodialysis at Dr Tadjuddin Chalid Hospital Makassar. The research design used was cross sectional. The sample in this study were all CKD patients undergoing hemodialysis at Dr Tadjuddin Chalid Hospital Makassar. The sampling technique used in this study was total sampling. The results shows that there is no connection between age and quality of life for chronic kidney disease patients undergoing hemodialysis therapy (p = 1,000> 0.05), no connection between gender and quality of life (p = 0.420). > 0.05), no connection between education and quality of life (p = 0.775> 0.05), there is a connection between the duration of hemodialysis with quality of life (p = 0.017 <0.05), and there is no connection between vascular access with quality of life (p. = 0.141> 0.05). The conclusion from the results of this study is that there is no connection between age, gender, education, occupation and vascular access with the quality of life of patients with chronic kidney disease, but there is a connection between the duration of hemodialysis with the quality of life of patients with chronic kidney disease in Dr. Tadjuddin Chalid Hospital Makassar.